Peran Perilaku Organisasi dalam Organisasi Mahasiswa: Studi Kasus Himpunan Mahasiswa Jurusan Manajemen Tahun 2024 - Rosdiyanti Rosdiyanti; Fany Rahma; Ilah Ilah; Intan Nuraini; Ibnu Khoir Ar Razak; Hilman Priyadi; Vera Maria (Global Leadership Organizational Research in Management, 2025)
Organizational behavior plays an important role in determining the level of success of the Management Student Association (HMJ Manajemen) organization. By implementing good organizational behavior, members of the organization can work together and communicate effectively, so that each work program can run smoothly and common goals are more easily achieved. In addition, positive organizational behavior can also increase the enthusiasm and activeness of members in participating in various activities. A comfortable and open organizational environment will make members feel appreciated, so that new ideas can emerge and be implemented properly. The decision-making process becomes more participatory and transparent when organizational behavior runs well, so that decisions taken can be accepted by all members. Interaction within the organization also helps members develop various important skills such as leadership, communication, and the ability to work in a team. Not only that, professional organizational behavior will strengthen the image and reputation of HMJ Manajemen on campus and off campus. This will make it easier for the organization to establish cooperation and gain support from various parties.